At-Tarbiyah Furusiyah Al-Islamiyah as a Model for Mental Development in Islamic Boarding School Education - Zuhrotul Mufidah; Syarifah; Nur Indah Sari; Umma Fatayati; Deka Ismayanti (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
The mental development of santri is a fundamental aspect of pesantren education in responding to the challenges of character building and the resilience of the younger generation in the contemporary era. At-Tarbiyah Furusiyah Al-Islamiyah, as a physical education program based on the Sunnah of the Prophet Muhammad (peace be upon him) such as horseback riding and archery, is considered relevant in integrating physical, mental, and spiritual dimensions. This study aims to analyze the implementation of At-Tarbiyah Furusiyah Al-Islamiyah in the mental development of students, as well as to identify supporting and inhibiting factors in its implementation. The study uses a descriptive qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation involving 24 informants, consisting of caregivers, administrators, trainers, and students. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that At-Tarbiyah Furusiyah Al-Islamiyah is effective in shaping spiritual mentalities (trust in God and sincerity), ideological mentalities (courage and loyalty), as well as disciplined and resilient mentalities (focus and toughness). The success of the program is supported by the strong pesantren culture and the enthusiasm of the students, while limitations in time, facilities, and parents' understanding become the main obstacles. This study contributes to enriching the study of Islamic physical education as a model for holistic and contextual mental development of students.